Pattern of Surgical Cases and its Management in Bacha Khan Medical Complex Shahmansoor Swabi - Amin, Arshad; Rahman, Faiz -Ur-; Junaid, Fazli; Nisar, Shahid (Journal of Gandhara Medical and Dental Science, 2017)
OBJECTIVE To study the pattern of general surgery cases and their management in Bacha Khan Medical Complex Shahmansoor Swabi. METHODS This descriptive cases-series study was conducted prospectively in general surgery department Bacha Khan Medical Complex Shahmansoor Swabi form jan, 2013 to Dec, 2015. There were 1200 patients in the series who were managed either conservatively or operated upon. All patients with symptoms suggesting a surgical disease and managed as a surgical case were included, while cases that were referred to other departments and those that left against medical advice were excluded. RESULTS Most of the patients had alimentary tract diseases 361(30%) followed by urinary tract diseases 264 (22%),superficial lumps 142 (11.8%), hernia 140 (11.7%), hepato-biliary-pancreatic diseases 116 (9.7%), breast diseases 55 (4.6%), scrotal diseases 41 (3.4%), thyroid diseases 28 (2.3%),salivary gland diseases 15 (1.3%), vascular diseases 8 (0.7%), thoracic diseases 2 (0.2%) and miscellaneous 28 (2.3%). A total of 604 (64.5%) patients were treated as elective cases and333 (35.5%). were treated as emergency cases. As many as 937 (74.08%) patient were treated by operations and 263 (21.92%) patients by conservative treatment, while 41 (3.41%) patients were referred. Seven patients expired, giving a mortality rate of 0.58%. CONCLUSION The commonest cause of seeking surgical care was alimentary tract diseases, followed by urinary tract diseases, superficial lumps, hernias, hepato-biliary-pancreatic diseases, breast diseases, scrotal diseases and thyroid diseases. Bacha Khan Medical Complex Shahmansoor Swabi is a newly established hospital catering to the needs of population of district Swabi and adjoining districts and areas.